The efficacy and safety of atherectomy combined with drug-coated balloon angioplasty vs. drug-coated balloon angioplasty for the treatment of lower extremity artery disease: a systematic review and meta-analysis - Suriyanto, Margareta Ginanti Ratna Indraswari; Pranata, Raymond; Kamarullah, William; Putra, Iwan Cahyo Santosa; Wahyudi, Dendi Puji; Karwiky, Giky; Sihite, Teddy Arnold; Akbar, Mohammad Rizki; Martha, Januar Wibawa; Hidayat, Syarief (Frontiers in Cardiovascular Medicine, 2024)
Background: This study aimed to systematically evaluate the efficacy and safety of atherectomy followed by drug-coated balloon angioplasty (A-DCB) in comparison with drug-coated balloon (DCB) angioplasty alone for the treatment of lower extremity artery disease (LEAD). Methods: Systematic literature search was performed using several online databases including MEDLINE (via PubMed), Europe PMC, and ScienceDirect databases from inception until February 21st, 2024. We included all studies comprised three main variables including A-DCB, DCB, and LEAD. The primary outcomes were primary patency and target lesion revascularization (TLR). Whereas secondary outcomes were all-cause mortality, post-procedural complications, and clinical characteristics. Results: A total of 15 studies (10 cohort studies and 5 randomized controlled trials studies) consisting of 1385 participants with mean age 68.7 ± 8.9 were included. In comparison with DCB alone, A-DCB was significantly associated with a higher risk of primary patency (RR=1.16 (95% CI=1.07–1.26); P<0.001; I2=20.9%, P-heterogeneity=0.221) and lower risk of TLR (RR=0.61 (95% CI=0.46–0.81); P<0.001; I2=0%, P-heterogeneity=0.475). Subgroup analysis showed that only directional, rotational, and laser atherectomy increased the probability of primary patency, but only rotational atherectomy decreased the risk of TLR. Regarding secondary outcomes, A-DCB was substantially associated with a lower likelihood of bailout stenting, any amputation, and major amputation, as well as higher ankle brachial index (ABI) following follow-up duration. Meta-regression analysis suggested that pre-intervention s (p=0.015) and pre-intervention Rutherford classification (p=0.038) were significantly affected the association between A-DCB and primary patency. Begg’s funnel plot and Egger’s test analyses indicated no publication bias in this meta-analysis. Conclusions: The addition of atherectomy improves primary patency and reduces the risk of TLR with similar safety outcomes.